Detecting High-energy Neutrino Minibursts from Local Supernovae with Multiple Neutrino Observatories - Ali Kheirandish; Kohta Murase (The Astrophysical Journal Letters, 2023)
Growing evidence from multiwavelength observations of extragalactic supernovae (SNe) has established the presence of dense circumstellar material in Type II SNe. Interaction between the SN ejecta and the circumstellar material should lead to diffusive shock acceleration of cosmic rays and associated high-energy emission. Observation of high-energy neutrinos along with the MeV neutrinos from SNe will provide unprecedented opportunities to understand unanswered questions in cosmic-ray and neutrino physics. We show that current and future neutrino detectors can identify high-energy neutrinos from an extragalactic SN in the neighborhood of the Milky Way. We present the prospects for detecting high-energy neutrino minibursts from SNe in known local galaxies, and demonstrate how the network of multiple high-energy neutrino detectors will extend the horizon for the identification of high-energy SN neutrinos. We also discuss high-energy neutrino emission from SN 2023ixf.